Harmoni Beragama dalam Tradisi Ogoh-Ogoh: Studi Kasus Pura Agung Satya Dharma Desa Sekaran Kediri - Huda, M Thoriqul; Al Akhya, Wafiq; Hardiyanti, Siti (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2024)
This study investigates the dynamics of religious harmony that occur in the ogoh-ogoh tradition at Pura Agung Satya Dharma, Sekaran Village, Kediri, through the lens of social interaction theory. Ogoh-ogoh, a Hindu ritual held before Nyepi Day, sets the stage for complex social interactions in the multireligious community of Sekaran Village. This study uses a qualitative approach with a focus on field data collection through observations, interviews, and documentation. The results highlight how the ogoh-ogoh tradition is not only a religious symbol for Hindus but also a point of convergence for other religious communities in building harmony and harmony amidst differences in beliefs. The analysis of the social interaction theory provides deep insights into how social relations, norms, and values influence each other in the context of ogoh-ogoh celebrations. The results show that the Sekaran village community is a multicultural and multi-religious village able to foster a sense of love, harmony, and harmony in religious activities such as the ogoh-ogoh celebration, which is a Hindu culture. Moreover, the ogoh-ogoh culture, which is held every year, brings the community closer in life. However, the weakness of this study lies in the limited representation of the sample, which may not cover the entire spectrum of the Sekaran community. In addition, this research may also be limited in considering external factors that could influence the dynamics of religious harmony in the ogoh-ogoh tradition, such as broader political, economic, and sociocultural factors. Therefore, the results of this study should be considered in light of these limitations in the context of its analysis.